Faith in Freedom : Propaganda, Presidential Politics, and the Making of an American Religion - Polk, Andrew R., 1980- (Book collections on Project MUSE., 2021)
"An investigation of the use of religious propaganda by the Franklin Roosevelt, Harry Truman, and Dwight Eisenhower administrations and their allies during World War II and the early Cold War to unite Americans behind their preferred policies"--